The Correlation Between the Level of Depression and Religious Coping Among Medical Students Class of 2020 Universitas Airlangga - Muhammad Al-Farouq Yufiro Akbar; Azimatul Karimah; Imam Susilo; Purwo Sri Rejeki (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Medical students are at risk of developing depression due to their demanding workload and high expectations, which can impact their academic performance and cognitive function. To prevent severe complications, students must prioritize resources for mental health support, namely religious coping as a coping mechanism. Objective: The aim of this study is proof the correlation between depression levels and religious coping in medical students class of 2020 Universitas Airlangga Methods: This research is an observational analytic study with a cross-sectional design, and random sampling was used as a sampling method, totaling to 90 subjects. Variables used were religious coping and level of depression. The data was then analysed and prevalence, correlation coefficient and p-value were acquired. The research result would be considered significant if p <0.05. Result: Out of 90 students, 32 people (35.6%) are found to have a PHQ score more than 10, indicating depression. Severity was found mostly have moderate depression, which consisted of 12 people (13.3%). For religious coping, 84 people (93.3%) use positive religious coping, and 6 people (6.7%) use negative religious coping. The level of depression correlates with religious coping with a Pearson correlation of -0.450, indicating a negative correlation with a p-value less than 0.001. Conclusion: The prevalence of depression among medical students class of 2020 Universitas Airlangga is 35.6%. Level of depression in found to significantly correlates with religious coping with an opposing direction of correlation.